Effect of the Method of Agitation on the Accumulation of Protective Antigen in Cultures of Bacillus anthracis - Wright, George G. (1971)
Accumulation of protective antigen was essentially independent of culture volume, provided the organisms were kept in suspension by stirring. Agitation by orbited shaking was unsatisfactory.